2012
DOI: 10.3109/02713683.2012.749917
|View full text |Cite
|
Sign up to set email alerts
|

Tear Osmolarity and Ocular Surface Changes in Patient with Polycystic Ovary Syndrome

Abstract: In patients with recently diagnosed PCOS, tear volume and osmolarity are not affected but, conjunctival morphology may be affected, though on a limited scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Particularly in these women there is a significant increase in signs and symptoms of DE. Not surprisingly, a high incidence of evaporative DE disease was found in hyperandrogenic women affected by syndrome of polycystic ovarian syndrome [40,41]. This allows us to speculate that for the tear film to be stable it is necessary a perfect balance between androgens and estrogens for a normal function [40,41].…”
Section: Hormonal Changesmentioning
confidence: 91%
See 3 more Smart Citations
“…Particularly in these women there is a significant increase in signs and symptoms of DE. Not surprisingly, a high incidence of evaporative DE disease was found in hyperandrogenic women affected by syndrome of polycystic ovarian syndrome [40,41]. This allows us to speculate that for the tear film to be stable it is necessary a perfect balance between androgens and estrogens for a normal function [40,41].…”
Section: Hormonal Changesmentioning
confidence: 91%
“…Androgens are steroid hormones that are produced by the adrenals (dehydroepiandrosterone demonstrated that androgen levels are essential for normal lacrimal gland function and structural organization and that prolactin and estrogens also play important roles in providing an adeguate hormone provision for optimal lacrimal production [39][40][41]. In particular, the androgen receptor influence the MGs, this has led to the hypothesis that these glands are under hormonal control.…”
Section: Hormonal Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…M aters et al reported a negative correlation betw een total testosterone and tear function in prem enopausal w om en, w hereas total testosterone correlated positively w ith tear function for w om en in m enopause (25) . O ne recent study, G onen et al (26) evaluated tear osm olarity test. T his study reported that there w as no significant difference betw een the m ean tear osm olarity values obtained from P (26) .…”
Section: Discussionmentioning
confidence: 99%